DESKRIPSI PENGADAAN BARANG ATAU JASA BERBASIS E-PROCUREMENT DI PT. PLN (PERSERO) AREA KEDIRI - Ayuningtias, Fitri (Jurnal Ilmiah Mahasiswa FEB, 2017)
The research aims to describe the procurement process of goods and services based  on e-procurement  procedure  in PT. PLN (Persero)  around  Kediri.  Such an online service  is implemented  to  give convenience  for  the users,  especially on the  information transparency, procedure, and cost and to increase the rate control of the society, government, and other relevant parties. Another benefit is to establish selective logging system, auction, competitive  bidding  price,  and  trusted goods  or  service  quality.  Those  advantages  can increase public confidence to the service provided by PT. PLN (Persero) and reduce fraud. This descriptive qualitative research applies a case study approach in which the data are obtained through observation, interview, document study, and literature review. The result of the analysis shows that e-procurement has run very well in the Persero of Kediri area and is in accordance with the procedure. PT. PLN of Kediri is able to carry out the principles of good corporate governance, accountabillity, but not on the aspect of transparency.Keyword : Evaluation, Procurement of goods and services, conventional, E-procurement